Differences of attacking pattern in winning and losing team in EURO 2016 / Muhamad Faiq Rusydi Mohd Rosdan - Mohd Rosdan, Muhamad Faiq Rusydi (2017)
Present study being conducted in order to determine any differences in tenn of attacking pattern between winning and losing teams in EURO 2016. 33 matches were selected excluding the draw matches. Five indicators being choose which were shot on target (outside penalty box, penalty box and goal box area), area shot on target (six areas have been divided), crossing, goal scoring time and area goals have been scored (six areas have been divided). Mann-Whitney used to prove differences between winning and losing teams with significant value was set at p < 0.05. Shot on target (Z = -3.603, p < 0.05), area shot on target outside penalty box (Z = -3.721, p <0.05), area shot on target goal box (Z = -2.078, p < 0.05). The highest goals scoring was at inside penalty box which were not too near from goal keeper and not too fur from goal post. Area shot on target B (Z = - 2.413, p < 0.05), area shot on target C (Z = -2.992, p < 0.05), area shot on target E (Z = - 2.678, p < 0.05) and area E was the highes shot from the players. Crossing (Z = -2.272, p < 0.05), scoring time 16-30 min (Z = -2.777, p < 0.05), 31-45 min ( Z = -2.749, p < 0.05), 46-60 min (Z = -2. I 74, p < 0.05), 76-90 min (Z = -4.383, p < 0.05) , area goal post A (Z = -2.775, p < 0.05), area goal post C (Z = -1.984, p < 0.05), area goal post D (Z = -3.790, p < 0.05), area goal post E (Z = -3.597, p < 0.05). Area goal post D was the highest goals noted during this toumarnent. The present data can be used by the coaches to conducted the various and specific training program depend on their objectives.